Besonderheiten bei der Auslegung und Gestaltung lasergesinterter Bauteile - Wartzack, Sandro; Drummer, Dietmar; Wittmann, Stefan; Stuppy, Julia; Rietzel, Dominik; Tremmel, Stephan; Kühnlein, Florian (RTejournal - Forum für Rapid Technologie, 2010)
UnivIS-Import:2015-03-09:Pub.2010.tech.FT.FT-KLMEFK.besond

Characterization of new thermoplastics for additive manufacturing by selective laser sintering - Rietzel, Dominik; Kühnlein, Florian; Drummer, Dietmar (68th Annual Technical Conference of the Society of Plastics Engineers 2010, ANTEC 2010, 2010)
Keywords: Additive manufacturing; Isothermal crystallization; PA2200; PE; POM; PP; Selective laser sintering

Degradation behaviour of PA 12 powders in laser sintering - Drummer, Dietmar; Kühnlein, Florian; Drexler, Maximilian (Proceedings of the 4th International Conference on Additive Technologies (ICAT 2012), 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KT.degrad

Development of a characterization approach for the sintering behavior of new thermoplastics for selective laser sintering - Drummer, Dietmar; Rietzel, Dominik; Kühnlein, Florian (Physics Procedia, 2010)
Currently the standard thermoplastic powders for selective laser sintering are based on polyamide12. This leads to restrictions for many applications e.g. in the industrial or medical field. Thus, research on further polymers with enhanced chemical or higher thermal stability plays a major role for applying additive manufacturing to serial production of individual components. Currently, great efforts are made to process new technical thermoplastics like polypropylene or polyetherketones by selective laser sintering. In this paper, the suitability and processing behavior by means of melting and (isothermal) crystallization are studied, and a method for the qualification of new materials is presented. Based on this method processing parameters for new thermoplastics can systematically be found. © 2010 Published by Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2010.tech.FT.FT-KT.develo
Keywords: Additive manufacturing; Isothermal crystallization; PA2200; PE; PEEK HP-3; POM; PP; Selective laser sintering

Effects on the density distribution of SLS-parts - Drexler, Maximilian; Kühnlein, Florian; Drummer, Dietmar (Physics Procedia 39, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KT.effect

Feasibility study of additive manufacturing of thermally conductive pa12 powders by selective mask sintering - Kühnlein, Florian; Rietzel, Dominik; Drummer, Dietmar (68th Annual Technical Conference of the Society of Plastics Engineers 2010, ANTEC 2010, 2010)
Keywords: Additive Manufacturing; PA 12 Powders; Rapid Prototyping; Selective Mask Sintering; Thermal Conductivity

Funktionalisierte Bauteile durch Selektives Maskensintern - Drummer, Dietmar; Kühnlein, Florian; Rietzel, Dominik (RTejournal - Forum für Rapid Technologie, 2009)
UnivIS-Import:2015-03-09:Pub.2009.tech.FT.FT-KT.funkti

Incremental In-line Measurement Technique for Additive Manufacturing - Hartmann, Wito; Hausotte, Tino; Kühnlein, Florian; Drummer, Dietmar (Proceedings, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.lfmt.increm

Influence of powder coating on part density as a function of coating parameters - Drexler, Maximilian; Kühnlein, Florian; Drummer, Dietmar (4th International Conference on Additive Technologies, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KT.influe

Influence of temperature fields on the processing of polymer powders by means of laser and mask sintering technology - Rietzel, Dominik; Drexler, Maximilian; Kühnlein, Florian; Drummer, Dietmar (Twenty Second Annual International Solid Freeform Fabrication Symposium An Additive Manufacturing Conference, 2011)
Besides their high potential for individual series-production, powder and beam based additive manufacturing technologies, like laser and mask sintering, are in general still restricted to prototyping applications. This is a result of multiple limitations concerning part properties (e.g. mechanical and geometrical), their insufficient reproducibility due to transient thermal conditions and the limited range of available materials. The main focal point of this paper is to show the influencing parameters (e.g. temperature fields in the building chamber) of powder-based thermoplastic processing technologies on part properties, like porosity and surface quality, and on the processability of further new polymers (e.g. polypropylene and polyoxymethylene
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KT.influe_6

Investigations of the directional mechanical properties and reasons of fracture of Mask Sintered PA12-components - Kühnlein, Florian; Rietzel, Dominik; Drummer, Dietmar (Zeitschrift Kunststofftechnik, 2012)
Keywords: Additive Manufacturing; Mechanical Properties; Reasons of Fracture; Selective Mask Sintering

Investigations on the degradation behaviour of PA 12 plastic powders - Influence of high temperatures on the moleculare weight - Drummer, Dietmar; Kühnlein, Florian; Meister, Steve; Drexler, Maximilian (Proceedings of the 13th RAPDASA annual international Conference, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KT.invest

Materialalterung beim Rapid Manufacturing - Alterungsverhalten von Kunststoffpulvern beim selektiven Strahlschmelzen - Wudy, Katrin; Kühnlein, Florian; Drummer, Dietmar; Drexler, Maximilian (GIT Labor-Fachzeitschrift, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-KT.materi

Mechanische Eigenschaften und Bruchverhalten maskengesinterter Kunststoffbauteile - Drummer, Dietmar; Kühnlein, Florian (Rapid.Tech 2011, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KT.mechan

Mechanische Eigenschaften und Bruchverhalten maskengesinterter Kunststoffbauteile - Drummer, Dietmar; Kühnlein, Florian (RTejournal - Forum für Rapid Technologie, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.FT.FT-KT.mechan_5

Modeling of Transient Thermal Conditions During Selective Laser Melting - Drexler, Maximilian; Kühnlein, Florian; Drummer, Dietmar (1st International Conference on Thermo-Mechanically Graded Materials, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KT.modeli

Polymer Blends for Selective Laser Sintering: Material and Process Requirements - Wudy, Katrin; Drummer, Dietmar; Kühnlein, Florian (Physics Procedia 39, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KT.polyme

Selektives Lasersintern von teilkristallinen Thermoplasten - Drummer, Dietmar; Rietzel, Dominik; Kühnlein, Florian (RTejournal - Forum für Rapid Technologie, 2009)
UnivIS-Import:2015-03-09:Pub.2009.tech.FT.FT-KT.selekt

Untersuchung der Materialalterung bei pulverbasierten Schichtbauverfahren - Drummer, Dietmar; Kühnlein, Florian; Rietzel, Dominik; Hülder, Gerrit (RTejournal - Forum für Rapid Technologie, 2010)
UnivIS-Import:2015-03-09:Pub.2010.tech.FT.FT-KT.unters_3

Untersuchung der richtungsabhängigen mechanischen Eigenschaften und Bruchursachen maskengesinterter PA12-Bauteile - Kühnlein, Florian; Rietzel, Dominik; Drummer, Dietmar (Zeitschrift Kunststofftechnik, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KT.unters